Calculation of the inductance of conductive nonmagnetic conductors by means of finite element method simulations. Issue 3 (July 2020) - Riba, Jordi-Roger; Capelli, Francesca
This article analyzes the inductance of different conductive nonmagnetic conductors' configurations under alternating current supply. The inductance is a key design parameter in tracks of electronic devices, power transmission and distribution systems, and lightning, grounding, and bonding systems. Inductance highly relies on the problem geometry, and under AC supply, it is also influenced by skin and proximity effects. The inductance significantly determines voltage drop in conductors, thus increasing reactive power consumption and limiting conductors' ampacity. Although this is an important topic, it is seldom studied in detail in undergraduate and even in graduate physics and engineering studies. To this end, this paper compares the results provided by existing closed formulas for simple conductors' configurations with those attained through two-dimensional finite element method simulations. Finite element method based simulations are increasingly being incorporated in the syllabuses of graduate and undergraduate courses due to their accurate solutions and flexibility, since finite element method models can be applied in a wide range of electrical frequencies and configurations, some of which do not have an analytical solution. The finite element method based approach presented in this paper has been found a valuable complement to the lectures and assignments in electricity courses for engineering students.